Mediasi Impulsivitas Dalam Pengaruh Keterampilan, Literasi Keuangan Digital Dan Otonomi Terhadap Kesejahteraan Keuangan - Tarigan, Liyandri Rasbina; Prabowo, Theresya Amelia (JEMAP, 2025)
This study aims to determine the effects of Skills on Financial Well-Being, Digital Financial Literacy on Financial Well-Being, Autonomy on Financial Well-Being, and Impulsivity on Financial Well-Being. It also aims to determine the role of Impulsivity in mediating the effects of Skills, Digital Financial Literacy, and Autonomy on Financial Well-Being. The population of this study is all people who have a fixed income or business activities that let them manage their finances on their own. In this study, the Structural Equation Modeling (SEM) method with an intervening relationship was used for data analysis. The data analysis tools were provided by the AMOS software version 26.  The findings of the analysis were as follows: Skills have an impact on financial well-being; Digital Financial Literacy has an impact on financial well-being; Autonomy has an impact on financial well-being; Impulsivity has an impact on financial well-being; Impulsivity can mediate the impact of Digital Financial Literacy on financial well-being; and Impulsivity can mediate the impact of Autonomy on financial well-being. The study's conclusions highlight how crucial it is to control impulsive behavior in order to optimize the advantages of skills, financial literacy, and autonomy. This provides useful advice for people, educators, and policymakers in promoting financial resilience